Esophageal perforation due to inadvertent swallowing of a dental prosthesis - Deniz TİHAN,; Didem TRABULUS,; Aykut ALTUNKAYA,; Selami KARACA,; Alper CİHAN,; Halil ALIŞ, (Turkish Journal of Gastroenterology, 2019)
-